THE EFFECT OF USING MIXTURE OF MEAT AND BONE OF EEL-TAILED CATFISH(Paraplotosus albilabris) IN FISH STICK PRODUCTION ON CONSUMER ACCEPTANCE - Thessa Amaria Sari; Desmelati Desmelati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABTRACK The purpose of this research is to know the effect of using mixture of meat and bone of eel-tailed catfish in fish stick production on consumer acceptance and find the best stick product from using mixture of meat and bone of eel-tailed catfish. This research used experimental method with non-factorial completely randomized design, with 4 kinds of treatment: sticks with 200 grams of meat (St0), sticks with 125 grams of meat and 75 grams of bone (St1), sticks with 100 grams of meat and 100 grams of bone (St2), and sticks with 75 grams of meat and 125 grams of bone (St3). The research parameters were organoleptic test (appearance, odor, taste, and texture) and proximate test (moisture, protein, fat, ash, and calcium). The findings showed that St1 sticks (using 125 grams of meat and 75 grams of bone) have the highest organoleptic value, involve the apperance (golden yellow colour), odor (seasoning and fishy smell), taste (the seasoning taste is the same specific as the fish taste), texture (very crunchy and savoury). Based on the best proximate value, St1 sticks (using 125 grams of meat and 75 grams of bone), contained 1,46% moisture, 11,53% protein, 26,59% fat, 3,44% ash, and 1,06% calcium.Keywords:diversification, fish stick, Paraplotosus albilabris.